Elevated CO₂ atmosphere promotes plant growth and inulin production in the cerrado species Vernonia herbacea - Oliveira, Vanessa F; Zaidan, Lilian B.P; Braga, Márcia R; Aidar, Marcos P.M; Carvalho, Maria Angela M (Functional plant biology : FPB, 2010)
Carbon allocation in biomass is an important response of plants to the increasing atmospheric [CO₂]. The effects of elevated [CO₂] are scarcely reported in fructan-accumulating plants and even less in tropical wild species storing this type of carbohydrate. In the present study, the effects of high [CO₂] atmosphere was evaluated on growth, biomass allocation and fructan metabolism in Vernonia herbacea (Vell.) Rusby, an Asteraceae from the Brazilian cerrado, which accumulates inulin-type fructans in the underground organs (rhizophores). Plants were cultivated for 120 days in open-top chambers (OTCs) under ambient (~380μmolmol⁻¹), and elevated (~760μmolmol⁻¹) [CO₂]. Plant growth, photosynthesis, fructan contents, and the activities of fructan metabolising enzymes were analysed in the rhizophores at Time 0 and 15, 30, 60, 90 and 120 days. Plants under elevated [CO₂] presented increases in height (40%), photosynthesis (63%) and biomass of aerial (32%) and underground (47%) organs when compared with control plants. Under elevated [CO₂] plants also presented higher 1-SST, 1-FFT and invertase activities and lower 1-FEH activity. Although fructan concentration remained unchanged, fructan productivity was higher in plants maintained under elevated [CO₂], due to their higher rhizophore biomass. This is the first report on the effects of elevated [CO₂] on a plant species bearing underground organs that accumulate fructans. Our results indicate that plants of V. herbacea can benefit from elevated atmospheric [CO₂] by increasing growth and carbon allocation for the production of inulin, and may contribute to predict a future scenario for the impact of this atmospheric condition on the herbaceous vegetation of the cerrado.